PENGARUH FAKTOR RISIKO, USIA, JENIS KELAMIN DAN STATUS IMUNISASI PADA KASUS TB PARU ANAK DI PUSKESMAS MERDEKA - Dianita Ekawati (KOLONI, 2022)
Pediatric tuberculosis is TB that occurs in children aged 0-14 years. TB cases that occur in children can be estimated annually to be 5% - 6% of the total TB cases. The highest child TB cases were in the city of Palembang, namely in the working area of the Puskesmas Merdeka as many as 157 cases (Palembang City Health Office, 2019). The purpose of this study was to analyze the factors that influence the incidence of child tuberculosis in the Working Area of the Puskesmas Merdeka, Palembang City. This study used a quantitative design with cross sectional. The number of samples was 157 respondents. The analysis technique was performed by using the Chi Square test with univariate, bivariate and multivariate data analysis. The analysis showed that there was a significant relationship between age (p value = 0.031), gender (p value = 0.005) and household contact (p value = 0.029). And there is no significant relationship between history of BCG immunization (p value = 0.240) with the incidence of tuberculosis in children. And the most dominant variable is age withPR